GAMBARAN PENGETAHUAN PERAWAT DALAM MELAKUKAN BANTUAN HIDUP DASAR (BHD) DIRUANGAN INTENSIVE CARE UNIT (ICU) RSUD DR. PIRNGADI MEDAN - Juliana Juliana; Selly Salsalina Br. Sembiring (Jurnal Online Keperawatan Indonesia, 2018)
Basic life support is the first effort done to maintain life when the patient experiencing a threatening situation.This research aims to know the description of knowledge nurses in conducting basic living assistance ICU area puplic hospital Dr.Pirngadi Medan.Methode use on the research is descriptive method with cross sectional design.Sampling technique used is total sampling technique with the number of samples of 27 respondents. The results of this study indicate the level of knowleadge of nurses who served in the ICU room in both categories good 19 people (70,4%), respndents who have enough knowledge that is 8 respondents (29,6%), and no respondents who have less knowledge.